PENGUATAN PERAN PEREMPUAN DALAM PENGELOLAAN HARTA PUSAKA TINGGI DI MINANGKABAU - Yuhelna Yuhelna; Sri Rahmadani; Waza Karia Akbar (LPPM Universitas Ekasakti, 2021)
The problem of managing inheritance in West Sumatra, especially in Minangkabau, is getting more and more difficult to resolve through deliberation to reach a consensus. This can be seen from the increasing number of cases of inheritance disputes in court. It cannot be denied that one of the causes is the weakening or decreasing role or involvement of women in the management of inheritance which is traditionally